Skewed intracellular cytokine production of iNKT cells toward Th2-related responses in alloimmunized thalassemia patients. (April 2021) - Amirian, Niloofar; Ranjbaran, Reza; Shokrgozar, Negin; Ataei, Saeed; Bazrafshan, Asghar; Sharifzadeh, Sedigheh
Highlights: The iNKT cell subsets showed an equal distribution in healthy individuals. There was a balance between two iNKT subsets in non-alloimmunized patients. There was a shift in iNKT cells towards IL-4 production in alloimmunized patients. iNKT cells might play an essential role in thalassemia patients' alloimmunization. Abstract: Introduction: Red blood cell alloimmunization is a challenging issue in thalassemia patients. Several studies have investigated the role of different immune system compartment in alloimmunization, but the exact mechanism remains unclear. Considering the immunoregulatory function of iNKT cells and their subsets, in this study, we evaluated the possible role of these cells in alloimmunization status of thalassemia patients. Methods: 78 β-thalassemia major patients (41 alloimmunized and 37 non-alloimmunized) and 17 healthy controls were engaged in this study. Mononuclear cells were isolated from peripheral blood samples and stimulated for cytokine production. Samples were subjected to flow cytometry for enumeration of iNKT cells and characterized based on their cytokine production pattern. Finally, the results correlated with alloimmunization status, clinical and laboratory data. Results: Results demonstrated that the number of iNKT, iNKT + IFN-ɤ+, and iNKT + IL-4 + cells in thalassemia group was significantly higher than healthy controls while no significant change was observed in the number of these cells between alloimmunized and non-alloimmunized thalassemia patients. Interestingly, the ratio of iNKT + IL-4 + : iNKT + IFN-γ + cells in alloimmunized thalassemia group represent a considerable increase in comparison to both non-alloimmunized thalassemia group and healthy controls. However, evaluating this value in non-alloimmunized group represents an approximately equal ratio of 0.94, which was almost similar to this ratio in the control group (0.99). Conclusion. Our results illustrated a noteworthy imbalance in the ratio of iNKT cell subsets in favour of IL-4 producing iNKT cells in alloimmunized thalassemia patients. Regarding the role of IL-4 in stimulating the Th2-related immune responses, this imbalance could consider as a possible mechanism in alloantibody responses of thalassemia patients.